Influence of Work Discipline, Work Environment, and Work Motivation On Employe Performance at Bank Syariah Indonesia (BSI) Palopo City - Hasria Hasria; Samsul Bachri; Indra Kusdarianto (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This research aims to analyze the influence of work discipline, work environment, and work motivation on employee performance at Bank Syariah Indonesia (BSI) Palopo City. Methodology: This study uses a quantitative approach with a survey method. The research population consists of all employees of Bank Syariah Indonesia (BSI) in Palopo City. The sampling technique used was saturated sampling, so the entire population was made respondents, totaling 50 people (n=50). Data analysis was conducted through validity tests, reliability tests, classical assumptions, and multiple linear regression with the help of SPSS version 26. Results: The research results show that work discipline, work environment, and work motivation have a positive and significant effect on employee performance, both partially and simultaneously. Findings: The findings confirm that improving work discipline, work environment, and work motivation is very important in enhancing employee performance. Novelty & Originality: This study offers novelty by examining these three variables in the context of a sharia bank in Palopo City, a regional setting rarely explored in prior research. Conclusions: The study concludes that integrated improvements in discipline, environment, and motivation are essential for optimizing employee performance. Type of Paper: This paper is an empirical research paper.